Examining The Role Of Social And Contextual Factors In Gratitude Expression Strategies Among University Students - Muhammad Shaique , Sardar Muhmmad , Dr. Muhammad Anees ul Husnain Shah , Hajra Arif , Jawad Karamat , Nazim Ali (Migration Letters, 2024)
The present study investigates the utilization of gratitude expression strategies by university students in Pakistan. This research advocates that understanding the influence of contextual and social variables is integral to pragmatic competence in gratitude expression. Employing a 10-situation Discourse Completion Task (DCT), data was gathered from 80 participants. Cheng’s (2005) taxonomy was utilized to analyze the strategies employed for exp[1]ressing gratitude. The findings revealed that the students possessed a repertoire of gratitude expression strategies. Furthermore, their responses exhibited distinct patterns contingent upon various contextual factors, such as the magnitude of the imposition and the social power dynamic. The most frequently employed strategies included expressions of thanks, appreciation, and positive emotions. Conversely, strategies such as offers of repayment, acknowledgment of the imposition, and others were rarely used, suggesting a potential deficit in pragmatic competence. The study concludes with a discussion of the implications for future research.